Stress Tolerant Rice And On-Farm Seed Production Ensure Food Security And Livelihood To Small And Marginal Farmers Of Sundarbans (Indian Site) - Chattopadhyay, K; Gayan, S; Mondal, I; Mishra, SK; Mukherjee, Ak; Reddy, JN; Marndi, BC; Sarkar, RK (SAARC Journal of Agriculture, 2020)
Natural calamities have adverse effects on the life of marginal and small farmer practicing rice cultivation in Sundarban areas. Through discussion and questionnaires opinion of farmers were obtained that was applied to mitigate the problem of rice cultivation. Rice varieties tolerant to stagnant flooding, submergence and salinity had great promise to improve food security and livelihoods of the poor farmers of Sundarban area. The study revealed that small and marginal farmers accepted the new varieties very readily if seeds were produced locally. Informal seed systems had better promise for small and marginal farmers live in fragile ecosystem of Sundarban. SAARC J. Agri., 17(2): 127-139 (2019)